2020
DOI: 10.33024/hjk.v13i4.1824
|View full text |Cite
|
Sign up to set email alerts
|

Stigma dan diskriminasi serta strategi koping pada orang dengan HIV dan AIDS (ODHA) di kota Medan, Sumatera Utara

Abstract: People living with HIV/AIDS (PLWHA), battling stigma, discrimination and coping strategies  in  Medan, IndonesiaBackground: People living with HIV/AIDS have a multiple problem, PLWHA has a decreased physical abilities effect immunodeficiency, but also having a psychological and social problems also increase their burden. The health provider should be a place for PLWHA to get the right information about HIV/AIDS, but they follow to stigmatize and discriminate against them.Purpose: To describe coping PLWHA face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
0
8
0
3
Order By: Relevance
“…(16) Factors related to coping strategies in facing various stresses internally and externally, PLWHA is expected to maintain positive coping in facing these challenges. Nurses, healthcare providers and citizens are expected not to stigmatize and discriminate for PLWHA, considering that this has an impact on HIV/AIDS treatment and prevention programs (1,26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(16) Factors related to coping strategies in facing various stresses internally and externally, PLWHA is expected to maintain positive coping in facing these challenges. Nurses, healthcare providers and citizens are expected not to stigmatize and discriminate for PLWHA, considering that this has an impact on HIV/AIDS treatment and prevention programs (1,26).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing problemfocused coping as well as the presence of social support may be useful for improving the quality of life among PLWHA who report high stigma (16) In the study of stigma and discrimination as well as coping strategies carried out in the city of Medan, North Sumatra, 4 coping themes were obtained, namely 1) Have experienced stigma and discrimination from health workers, 2) Have experienced psychological impacts, 3) Continue to continue treatment to health services, 4) Expectations on health services. Furthermore, it was concluded that PLWHA in the city of Medan still have positive coping in facing stigma and discrimination so they can continue to receive treatment in health services (1).…”
Section: Research From Emmanuel (2019)mentioning
confidence: 99%
See 2 more Smart Citations
“…Pettit (2008) menjelaskan bahwa isu yang perlu dihadapi pasien tidak hanya isu kesehatan, namun juga isu stigma sosial yang seringkali diasosiasikan pada pasien. Beberapa penelitian telah dilakukan untuk mengetahui dampak stigma terhadap individu dengan isu kesehatan tertentu, seperti HIV-AIDS (Hasibuan, Aryani & Simajuntak, 2019) dan gangguan mental (Michaels, Lopez, Rusch, & Corrigan, 2012). Pettit (2008) mencoba menelusuri sejarah keterkaitan antara stigma dan penyakit hingga akhirnya menemukan bahwa permasalahan tersebut telah ada sejak tahun 1900-an sejak adanya penyebaran penyakit tertentu dari individu ke masyarakat.…”
Section: Diskusiunclassified